Bordetella bronchiseptica pneumonia a thread in the diagnosis of human immunodeficiency virus infection - Sonali Gupta; Pradeep Goyal; Joseph Mattana (IDCases, 2019)
Bordetella (B.) bronchiseptica is primarily a zoonotic pathogen, which is often found in upper respiratory tract of various domestic and wild animals. Human infections are rarely reported in immunocompromised patients and are associated with a wide spectrum of presentation ranging from mild cough, tracheobronchitis to sepsis and death. Here, we describe a case of B. bronchiseptica pneumonia that led to the diagnosis of human immunodeficiency virus infection.The diagnosis of B. bronchiseptica infection can be challenging, as there are no distinctive imaging features. This infection mimics Pneumocystis jiroveci infection and unless a detailed evaluation of an unusual presentation is done it may be missed, resulting in increased morbidity and mortality. This case emphasizes the importance of a systematic detailed investigation of patients with unusual pneumonia presentations. Keywords: Bordetella bronchiseptica, Pneumonia, HIV